Cutaneous leiomyosarcoma misdiagnosed as a keloid: A case report with dermatoscopy - Seher Bostancı; Bengu Nisa Akay; Merve Alizada; Aylin Okçu Heper (Galenos Publishing House, 2023)
Cutaneous leiomyosarcoma (CLMS), with an annual incidence of 0.2/100,000, is a very rare non-melanoma skin malignancy. CLMS has two subtypes: Dermal (primary) and subcutaneous; when diagnosed in the early period, the prognosis in the dermal type is better. CLMS is generally seen in the 6th and 7th decades of life and more frequently in the lower extremities and head and neck. Trauma, radiation, chemicals, and sun rays have been reported as the factors involved in its etiology. Epidermal cysts, skin metastases, dermatofibrosarcoma pro-tuberans, and keloid should be considered in the differential diagnosis of CLMS, which usually manifests as a nodular lesion. In the presented case, the lesion, which developed over scar tissue was diagnosed as keloid and treated accordingly for four years. The pathologic examination of dermal CLMS (d-CLMS) in this patient, in whom diagnosis was delayed, revealed invasion of the subcutaneous fat tissue, which is among the poor prognostic factors. Herein, we present a case with d-CLMS, in which early recognition is vitally important, who was treated for an extended period as keloid, and we emphasize the differential diagnosis in CLMS and pathological and dermatoscopic features that, to our knowledge, are being reported here for the first time.